2023
DOI: 10.1007/s10554-023-02806-0
|View full text |Cite
|
Sign up to set email alerts
|

Deep learn-based computer-assisted transthoracic echocardiography: approach to the diagnosis of cardiac amyloidosis

Abstract: Myocardial amyloidosis (CA) differs from other etiological pathologies of left ventricular hypertrophy in that transthoracic echocardiography is challenging to assess the texture features based on human visual observation. There are few studies on myocardial texture based on echocardiography. Therefore, this paper proposes an adaptive machine learning method based on ultrasonic image texture features to identify CA. In this retrospective study, a total of 289 participants (50 cases of myocardial amyloidosis; H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…When it comes to cardiovascular diseases, AI also plays an important role in their diagnosis. From the acute diagnosis of left ventricular hypertrophy using imaging methods such as echocardiography [ 56 ], to the diagnosis of amyloidosis also based on TTE [ 66 ] or idiopathic pulmonary hypertension [ 157 ], artificial intelligence has demonstrated its power to help clinicians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When it comes to cardiovascular diseases, AI also plays an important role in their diagnosis. From the acute diagnosis of left ventricular hypertrophy using imaging methods such as echocardiography [ 56 ], to the diagnosis of amyloidosis also based on TTE [ 66 ] or idiopathic pulmonary hypertension [ 157 ], artificial intelligence has demonstrated its power to help clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang X. et al showed in a retrospective analysis of 289 patients that ultrasonic imaging omics and a machine learning model can provide an excellent and non-invasive diagnostic tool for clinical practice for distinguishing CA from non-CA. For left ventricular strain, the machine learning model was slightly better than conventional echocardiography [ 66 ]. Another study, which analyzed 128 patients with ATTR-CA using AI, concluded that the ANN model estimated the risk of death or transplantation in patients with ATTR cm with better accuracy compared to traditional risk models [ 67 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The application of ML for automated analysis for medical purposes is gaining signi cant interest, particularly in clinical diagnostics that rely on EEG data (Gemein et al, 2020). These techniques has been widely used in various elds of medicine such as seizure detection (Jiang et al, 2022;Thakare et al, 2023) and emotion recognition (Fang et al, 2021;Yalamanchili et al, 2022) using EEG data, diagnosis of cardiac disease using electrocardiograph (Sharma et al, 2023;Zhang et al, 2023), and also image classi cation (Menaka and Vaidyanathan, 2022;Samraj et al, 2023). In this research, we examined three ML methods with the top 40 features extracted from hctsa to assess the differences between healthy individuals and those with MA dependence.…”
Section: Introductionmentioning
confidence: 99%